2001
DOI: 10.1109/25.917911
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance analysis of a data-reduction algorithm for automotive multiplexing

Abstract: Automotive multiplexing allows sharing information among various intelligent modules inside an automotive electronic system. In order to achieve an optimum functionality, the information should be exchanged among various electronic modules in real time. Data-reduction techniques are used to send the data over a transmission medium at a high speed. They can be employed in automotive multiplexing systems to improve the information exchange rate among various intelligent modules. Some off-the-shelf data-reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A second option is the generation of two new standard connection management messages with data compression at the transport level, e.g., TP.CM_RTS.DC and ETP.CM_RTS.DC, one for each transport protocol respectively using reserved 18 10 and 24 10 control bytes of the ISO 11783 standard. Finally, a third option is the use of the R bit as proposed in (Misbahuddin et al, 2001) for the data compression signaling on J1939 networks. Taking into account that the introduction of new data compression services within the ISO 11783 standard should be as transparent and simple as possible to prevent messages loses when bus utilization is close to 100%, the third option involving the use of the R bit is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…A second option is the generation of two new standard connection management messages with data compression at the transport level, e.g., TP.CM_RTS.DC and ETP.CM_RTS.DC, one for each transport protocol respectively using reserved 18 10 and 24 10 control bytes of the ISO 11783 standard. Finally, a third option is the use of the R bit as proposed in (Misbahuddin et al, 2001) for the data compression signaling on J1939 networks. Taking into account that the introduction of new data compression services within the ISO 11783 standard should be as transparent and simple as possible to prevent messages loses when bus utilization is close to 100%, the third option involving the use of the R bit is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Data Reduction (DR) algorithm [12], Adaptive Data Reduction (ADR) algorithm [13], Improved Adaptive Data Reduction (IADR) algorithm [14] and Enhanced Data Reduction (EDR) algorithm [15] fall under the second category. After evaluation of many text compression methods, the authors [10] found out that Huffman coding and Common Data stream Reference (CDR) coding were promising candidates for data compression in automotive body electronics.…”
Section: ) Dr Algorithms For Text Data 2) Dr Algorithms For Hexadecimentioning
confidence: 99%
“…They eliminated the message duplication error thus avoiding the mismatch in code tables at the transmission and reception ends. The DR algorithms that fall under the second category are based on CAN protocol (II-bit identifier) except for the DR algorithm [12] which is based on SAE Jl939 protocol. SAE Jl939 protocol is based on CAN 2.0 B (29-bit identifier).…”
Section: ) Dr Algorithms For Text Data 2) Dr Algorithms For Hexadecimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the first seven bytes of 8 bytes data do not change, the DCC code is shown in figure 3. Fig.3 The configuration of CAN data frame in MDR The core idea of data compression algorithm [9] is to reduce the data transmission. When the new message compared with the previous message, if some data content did not change, one bit can be used to represent a byte of data by setting corresponding bit in data compression encoding (DCC), DCC field in MDR algorithm occupied a byte of data , so only when the new information has more than one byte of data changed compared to the backup, the data compression technology MDR can be meaningful.…”
Section: Controller Design With Data-reduction Algorithmmentioning
confidence: 99%